Limited liability through registered companies and patnerships / Mahdi Yusuf - Yusuf, Mahdi (Faculty of Law, 1982)
The historical introduction deals primarily with the struggle to achieve limited liability that took place in England. It is of the writter's View that this is important so as to see and understand the present application of this concept. Although the U.K. Companies Act was passed in 1862, it was not until the case of Salomon V Salomon (1897) that the English courts had full grasp of the existence of a corporate entity conferred by the Act. Chapter II of the paper: deals with the privilege of limited liability through companies registered under the Companies Act, 1965. A duly registered limited company allows members to reap the advantage of limited liability while enjoying a varying rates of dividands. However, the concept of limited liability is not incapable of being removed. There are instances of such removal. In the case of partnership, though the liabilities of partners are joint and unlimited, it will be seen in Chapter III that an investor may enjoy a sort of limited liability. There is no doubt that partners are liable to the last cent of their fortune, but this is not so in the case of a bona fide lender. To put it simply, one can go ahead and invest in partnership but never be a partner there of and so escape personal liability. It is true to say that the ability to enjoy limited liability has turned the scale in favour of incorporation. However limited liability is not full—proof and not without its attendant costs. These shall be seen in the concluding Chapter.